PENGARUH MODEL PEMBELAJARAN SYNECTICS TERHADAP KEMAMPUAN MENULIS PUISI BAHASA INDONESIA PADA SISWA KELAS V SDN 1 BANGKELEKILA’ KABUPATEN TORAJA UTARA - Nur Abidah Idrus; Yusnadi; Pala, Jefrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the issue of students’ low ability in writing poetry. The objectives of this research were: (1) to describe the implementation of the synectics learning model in fifth-grade elementary school students; (2) to determine students’ poetry writing skills before and after the application of the synectics learning model; and (3) to examine the effect of the synectics learning model on the poetry writing skills of fifth-grade students. This research employed a quantitative approach using an experimental method and a quasi-experimental design with the nonequivalent control group design type. The population of this study was all fifth-grade students at SDN 1 Bangkelekila’, consisting of two classes which also served as the sample: class V A and V B, with a total of 46 students. The sampling technique used was purposive sampling, with class V A as the experimental group and class V B as the control group. Data collection techniques included tests, observation, and documentation. The data were analyzed using descriptive and inferential statistical analysis with the Independent sample t-test. The results from the experimental class showed: (1) the learning process using the synectics model was implemented with a “fair” category in the first meeting and a “good” category in the second meeting; (2) students’ poetry writing ability improved after the implementation of the synectics learning model, as evidenced by higher post-test scores compared to pre-test scores; and (3) the synectics learning model had a significant effect on the poetry writing skills of fifth-grade students at SDN 1 Bangkelekila’, North Toraja Regency. It can be concluded that the application of the synectics learning model significantly impacts poetry writing ability and leads to improvement in students’ test results.